Chemosymbiotic bivalves from Miocene methane-seep carbonates in Italy. (23rd March 2017) - Kiel, Steffen; Taviani, Marco
Abstract: Eleven species of chemosymbiotic bivalves are reported from middle to late Miocene methane seep deposits ('Calcari a Lucina ') in the Italian Apennines, including seven new species and one new genus. The new species are Bathymodiolus (s.l.) moroniae and B . (s.l.) miomediterraneus among the Bathymodiolinae and Archivesica aharoni, A . apenninica, A . strigarum, and ' Pliocardia ' italica among the Vesicomyidae; specimens from the middle Miocene of Deruta are reported as Archivesica aff. aharoni . Samiolus iohannesbaptistae new genus new species is introduced for an unusual mytilid with a commarginally ribbed surface, which might be the first non-bathymodiolin mytilid obligate to the seep environment. The two large lucinid species from which these deposits derived their informal name 'Calcari a Lucina ' are identified as Meganodontia hoernea (Des Moulins, 1868) and Lucinoma perusina (Sacco, 1901). With Chanellaxinus sp., we report the first thyasirid from a Neogene deep-water seep deposit in Italy and the first fossil occurrence of this genus.